Site Suitability Analysis for Provision of Ecosystem Services for Sustainable Waterfront Development - Mazed Parvez; Md Sazzadul Karim; A H Md Mahabub Nawaz; Syed Tanim Ahmed; Faisal M Ahamed; Md Fazle Rabby; Laila Begum (Research Synergy Foundation Press, 2024)
The